Port Needles: Do They Need to be Removed as Frequently in Infusional Chemotherapy? - YUMUK, PERRAN FULDEN (My University, 2003)
Proctracted chemotherapy regimens are new treatment modalities used to treat patients with cancer. These treatments are preferred because of the ease of administration and limited side effects in the outpatient setting. Sixty patients were treated with continuous infusion chemotherapy via implanted infusion ports at Marmara University Hospital Outpatient Chemotherapy Unit in Istanbul, Turkey, from January 2000 to December 2001. Although usage of Huber needles for central venous catheters was limited to between 48 and 72 hours, needles were not removed unless there were signs of inflammatory reaction. The needles remained in place for 28 days (1-49 days) on average. No catheter infections, signs of local irritation, or thrombus formation were observed despite prolonged stay of the Huber needles. Huber needles can be left in place up to several weeks without any untoward effects as long as proper aseptic technique is used.